2018
DOI: 10.1186/s40709-018-0088-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profile of urinary exosomes in Type IV lupus nephritis complicated by cellular crescent

Abstract: BackgroundType IV lupus nephritis (LNIV) is a severe disease characterized by diffuse proliferative lesions, and its prognosis is worse with cellular crescent (LNIV-CC) involvement. Urinary exosomes have been shown to reflect the degree of kidney injury. This study was aimed to identify non-invasive diagnostic markers for LNIV-CC. We analysed the expression profile of microRNAs (miRNAs) isolated from urinary exosomes in patients with LNIV-CC and LNIV, and healthy individuals using high-throughput sequencing.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
0
23
0
1
Order By: Relevance
“…7,8 The gold standard for diagnosis is an invasive renal biopsy, but this process could result in serious complications of variable severity and cannot be performed frequently in patients with DM. 9 Therefore, screening for specific and sensitive biomarkers is urgently needed for the early diagnosis of DKD and long-term monitoring of progression to ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The gold standard for diagnosis is an invasive renal biopsy, but this process could result in serious complications of variable severity and cannot be performed frequently in patients with DM. 9 Therefore, screening for specific and sensitive biomarkers is urgently needed for the early diagnosis of DKD and long-term monitoring of progression to ESRD.…”
Section: Introductionmentioning
confidence: 99%
“…Lupus nephritis is characterized by downregulation of urinary exosomal miR-29c [ 77 ] and upregulation of miR-146a [ 78 ], miR-150, and miR-21 [ 77 ]. A decrease in miR-21 along with let-7a miRNA precursor may indicate disease flare [ 79 ]; an increase in urinary exosomal miR-3135b, miR-654-5p, and miR-146a-5p has been described in cellular crescent formation of lupus nephritis [ 80 ]. Conversely, higher urinary exosomal levels of miR-31, miR-107, and miR-135b-5p are associated with a better response to treatment [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the anti-inflammatory miRNAs (i.e., let-7a and miR-21) were down-regulated in urinary exosomes derived from patients with LN and might serve as the non-invasive biomarkers to classify the clinical stage of LN (Tangtanatakul et al, 2019). Furthermore, urinary exosomal miR-3135b was increased in patients with active LN class IV as compared to those with inactive LN class IV and healthy controls, whereas miR-654-5p was increased only in LN class IV with cellular crescent (with very poor prognosis) (Li et al, 2018b). For other glomerular diseases, a previous study using a proteomics approach has shown that urinary exosomal aminopeptidase N, vasorin precursor, a-1-antitrypsin, and ceruloplasmin could differentiate immunoglobulin A (IgA) nephropathy from thin basement membrane nephropathy and healthy controls (Moon et al, 2011).…”
Section: Lupus Nephritis and Other Glomerular Diseasesmentioning
confidence: 97%